Konflik dan Integrasi: Potret Keagamaan Masyarakat Sawangan - Ulfah Fajarini (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2005)
This study is an antropological analysis on conflicts and integrations in percieving the teachings of Islam between Nahadlatul Ulama (NU) followers who base their perception on the Ahlusunnah wal Jamaah doctrines and the Muhammadiyah followers who in some way or other are influenced by Wahabid doctrines, among the communities living at Sawangan, Depok, West Java. Among the Sawangangan communities the two groups are significantly distinct able due tho their different interpretations as practical guidance in reacting to matters pertaining in their social life, so that teher seems to be two separate social structures. Inspite of the seperation phenomenans there are other phenomennas showing integrations in actions and attitudes toward matters constitute common interesr, for example in reacting toward prostution and gambling practices which both of the two groups think as factors corrupting the morality of the younger generation and also integrating their energy for common interest uniting local social structure.